University Students’ Preferences for Labour Conditions at a Mining Site: Evidence from Two Australian Universities - Ito, Yutaka; Mikami, Shuto; Jang, Hyong Doo; Taheri, Abbas; Tanaka, Kenta; Kawamura, Youhei (MDPI AG, 2020)
The mining industry makes up a large portion of the gross domestic product (GDP) in Australia, although securing human resources remains a problem in that field. The aim of this paper is to identify Australian university mining students’ preferences, considering it as potential employees’ preferences, for labour conditions at mining sites by means of a discrete choice experiment to promote efficient improvements in labour conditions in the mining industry. The data of 93 respondents analysed in this paper was collected by survey carried out in two universities in Australia. The result of the study showed that students have preferences on several factors such as wage, fatality rate, working position, commuting style, and company. Students having specific sociodemographic characters were found to show specific preferences on labour conditions. The results of this study indicate the potential average of appropriate monetary compensation for each factor.